THAHARAH: MAKNA ZAWAHIR DAN BAWATHIN DALAM BERSUCI (PERSPEKTIF STUDI ISLAM KOMPREHENSIF) - Ahmad, Mohammad Shodiq (MIZAN: JOURNAL OF ISLAMIC LAW, 2014)
Thaharah: Meaning Zawahir and Bawathin In Purification. Islam comprehensively stated that purification spawned many traits, attitudes, values and messages that would affect a person's behavior. Many hadiths that explain the virtues thaharah, which if carried out could remove sin and human error. In addition thaharah implicated in a variety of dimensions, such as the dimensions of Muamalat, morals, faith and so forth. Therefore, if thaharah or purification is always practiced as Sunnah, then it will be able to bring physical and spiritual purity.